KORELASI HIPERTENSI PADA MENOPAUSE DENGAN KEJADIAN INSOMNIA DI DESA TAMBAK ANYAR ILIR KECAMATAN MARTAPURA TIMUR KABUPATEN BANJAR - Devina Yolanda; Erni Yuliastuti; Erni Setiawati; Suhrawardi; Efi Kristiana (Bajang Institute, 2024)
Reproductive health problems at an advanced age in women appear when the fertile period ends (menopause). 2/3 of hypertension sufferers are women aged 45-70 years. Hypertension causes various symptoms related to menopause, including sleep disorders. Data from Puskesmas Martapura Timur in November 2018, Hypertension had an incidence of 143 cases including 102 cases (71.3%) experienced by 45-year-old women to the elderly. A total of 42 people (8.0%) hypertensive women were found in desa Tambak Anyar Ilir. The fact that the prevalence of elderly insomnia is found to be 54% for women and the between correlation the quality of sleep and blood pressure. The purpose of this study was to determine the correlation of hypertension in menopause with the incidence of insomnia in desa Tambak Anyar Ilir, Banjar Regency in 2019. The design of this study is an analytical survey with a cross sectional approach. The population of this study were all menopausal women in the Anyar Ilir Tambak village of 155 people. The sampling technique uses total sampling. The subjects in this study were menopausal women who were life in desa Tambak Anyar Ilir as many as 155 people. The research instrument used the Insomnia Scale Indexs (ISI) questionnaire. Data analysis used chi Square test. The results showed that of 155 respondents, 74 people (47.7%) had hypertension and 50 respondents (32.2%) had insomnia. Chi Square statistical test was obtained ρ value (0.023) <α (0.05) indicating that there was a significant correlation between hypertension in menopause with the incidence of insomnia and Odds Ratio = 2.24 and 95% Confidence Interval.